COVID-19: What Is Next for Portugal? - Shaaban, Ahmed Nabil; Peleteiro, Barbara; Martins, Maria Rosario O. (Frontiers in Public Health, 2020)
Highly infectious with the possibility of causing severe respiratory complications, the novel COVID-19 began stretching health systems beyond their capacity all over the world and pushing them to breaking points. Giving the devastating effects caused by this infection, unprecedented measures have to be adopted in order to mitigate its impacts on the health system. This perspective aims to review the epidemic of COVID-19 in Portugal, possible areas of improvement, and potential interventions that can help to mitigate the effect of COVID-19 on the Portuguese health system.